Satellite Image Gap Filling Technique - Mohammed, Faisel (Iraqi Journal of Science, 2024)
In the current research work a useful gap filling method was presented. Images overAl Mosel city in Iraq were used as tested images. The linear algorithm for highresolution (H.R.) image interpolation were based. The difference between theproposed algorithm and conventional nearest neighbor algorithm is that the conceptapplied, to estimate the missing pixel value, is guided by the nearest value ratherthan the distance. In other words, the proposed concept selects one pixel, amongfour directly surrounding the empty location, whose value is almost equal to thevalue generated by the conventional bilinear interpolation algorithm. Theexperimental results show that the proposed method demonstrated higherperformances in terms of H.R. and thus is applicable to gray level satellites images.